On a classification of word problems from the first grade Lithuanian textbooks - Kilienė, Ieva (Lietuvos matematikos rinkinys, 2021)
Word problems are classified to S problems and P problems by Verschaffel [9], classification is being specified and expanded. Reviewed word problems in Lithuanian first grade textbooks and divided to types. Submitted recommendations to use more varied types word problems, that would let to expand concepts understanding, develop mathematical reasoning, motivate to study word problem.
Keywords: Word problems; textbooks; P problem; S problem; mathematical reasoning